2020
DOI: 10.1002/ehf2.12561
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sodium zirconium cyclosilicate for hyperkalaemia: the randomized, placebo‐controlled HARMONIZE‐Global study

Abstract: Aims Sodium zirconium cyclosilicate (SZC, formerly ZS‐9) is a selective K+ binder to treat adults with hyperkalaemia. HARMONIZE‐Global examined the efficacy and safety of SZC among outpatients with hyperkalaemia from diverse geographic and ethnic origins. Methods and results This phase 3, randomized, double‐blind, placebo‐controlled study recruited outpatients with serum K+ ≥5.1 mmol/L (measured by point‐of‐care i‐STAT device) at 45 sites in Japan, Russia, South Korea, and Taiwan. Following open‐label treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 16 publications
8
55
1
Order By: Relevance
“…80 In randomized, placebo-controlled studies of patients with hyperkalemia, serum K þ concentrations were significantly reduced over 4 weeks with twice-daily patiromer [81][82][83] and were maintained within the normal range for a further 8 weeks 83 or for up to 52 weeks 81 with ongoing treatment. In randomized studies of SZC in patients with hyperkalemia, serum K þ concentrations were significantly reduced within 48 hours with 3-times-daily administration of SZC, [84][85][86][87] and normokalemia was effectively maintained for 12 to 28 days with once-daily SZC. [85][86][87] The long-term efficacy and safety of SZC as maintenance therapy for up to 12 months also has been shown in an open-label study of outpatients with hyperkalemia.…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%
See 1 more Smart Citation
“…80 In randomized, placebo-controlled studies of patients with hyperkalemia, serum K þ concentrations were significantly reduced over 4 weeks with twice-daily patiromer [81][82][83] and were maintained within the normal range for a further 8 weeks 83 or for up to 52 weeks 81 with ongoing treatment. In randomized studies of SZC in patients with hyperkalemia, serum K þ concentrations were significantly reduced within 48 hours with 3-times-daily administration of SZC, [84][85][86][87] and normokalemia was effectively maintained for 12 to 28 days with once-daily SZC. [85][86][87] The long-term efficacy and safety of SZC as maintenance therapy for up to 12 months also has been shown in an open-label study of outpatients with hyperkalemia.…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%
“…In randomized studies of SZC in patients with hyperkalemia, serum K þ concentrations were significantly reduced within 48 hours with 3-times-daily administration of SZC, [84][85][86][87] and normokalemia was effectively maintained for 12 to 28 days with once-daily SZC. [85][86][87] The long-term efficacy and safety of SZC as maintenance therapy for up to 12 months also has been shown in an open-label study of outpatients with hyperkalemia. 88 Studies in patients undergoing maintenance HD have indicated that these new K þ -binders may have a potential role in the management of these patients, including 2 studies with patiromer (an observational study and a retrospective cohort study) 2,89 and 1 randomized, doubleblind, placebo-controlled study with SZC (Table 3).…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%
“…Apart from one small prospective study in patients receiving hemodialysis, 79 the studies described in this section included predialysis patients with CKD receiving RAAS inhibitor therapy (Tables 4 and 5). 52,53,[55][56][57][58]78,80 Some study protocols specified K þ -controlled diets or advised restricted diets, 52,53,79 while others had no such dietary restrictions. 55,56,58,78 Sodium Polystyrene Sulfonate In a 2015 RCT in which 33 patients with CKD (nondialysis-dependent) and serum K þ concentrations of 5.0 to 5.9 mEq/L received double-blind treatment with oral sorbitol-free SPS or placebo for 7 days, SPS was superior to placebo in reducing serum K þ (between-group difference, 1.04 mEq/L; P<.001) without a significant difference in gastrointestinal adverse events between the groups.…”
Section: Clinical Efficacy and Safety Of K þ Binders For The Treatmenmentioning
confidence: 99%
“…76,77 Sodium Zirconium Cyclosilicate Phase 2 and phase 3 studies have investigated the efficacy and safety of SZC for the treatment of hyperkalemia in a wide range of patients, including a high proportion of patients with CKD receiving RAAS inhibitor therapy (Table 4). 55,56,58,78,80 In these studies, patients received doses of SZC ranging from 0.3 to 10 g thrice daily for a short period (ie, 24-72 hours) to normalize serum K þ concentrations (the correction phase), then continued SZC up to 15 g once daily for a period (ie, w2 weeks to 12 months) to maintain normokalemia; no dietary restrictions were imposed, and patients were not provided with any protocoldirected dietary advice. 55,56,58,78 More than 50% of patients received RAAS inhibitor therapy in the trials, 55,56,58,78 which was kept at a constant dose in 2 studies.…”
Section: Clinical Efficacy and Safety Of K þ Binders For The Treatmenmentioning
confidence: 99%
“…The recent phase 3, randomized, double-blind HARMONIZE-Global trial examined the efficacy and safety of SZC among outpatients with hyperkalemia, from diverse geographic and ethnic origins [74].…”
Section: Efficacy Datamentioning
confidence: 99%